Domesticity and consumer culture in Iran : interior revolutions of the modern era - Karimi, Z. Pamela (Iranian studies (London, England) ;, 2013)
"Exploring the process of Iran's modernization through the double lens of domesticity and consumer culture, Pamela Karimi demonstrates the extent to which the Iranian house has served as the place of encounter with the "other" and of reconsideration of the nation as "home." Domesticity and Consumer Culture in Iran examines the interplay between native aspirations, foreign influences, gender roles, consumer culture and women's education as they intersect with taste, fashion, domestic architecture and interior design in modern Iran. Throughout, ideas of consumer culture and gender are at its core, but other important socio-political subjects are examined in order to view Iran's modernization through the prism of its people's private lives. Presenting a new perspective on the 1979 Iranian revolution, re-read vis-à-vis the opinions of Shiite religious scholars, the Left, and the revolutionary elites , this book demonstrates how Iranians have contested the public-private dichotomy as manifested in the Islamic Republic's texts, images, and actual physical spaces"--